STUDENT PRIVACY AND FIRST AMENDMENT RIGHTS (STUDY RIGHTS IN ISLAMIC EDUCATION) - Nurul Oktaviana Mekawati; Herianto Herianto; Amiruddin Siahaan; Inom Nasution (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Privacy is a basic thing inherent in every human being, including students. Laws that apply in every part of the country, including Indonesia, agree to protect human rights and fulfill the rights of every citizen. This study aims to analyze student privacy and education policy as a study of student rights in the perspective of Islamic education. The approach of this research is using qualitative with literature study method. Sources of data and study analysis materials were obtained from credible relevant scientific literature. The credible search pages that the researchers classify include google scholar, DOAJ, science direct, tandfonline, and moraref. The results of this study found that students have a high curiosity and express all their desires freely. This free desire is a separate limitation for students, so that they do not conflict with ethical and social norms that apply in society. On this basis, laws or policies related to discipline and discipline for students must be fair, equal, and egalitarian. Thus, students' rights are still fulfilled to develop self-potential expressively, and are directed at positive things according to the applicable regulations in educational institutions.